Saikosaponin-d Suppresses COX2 Through p-STAT3/C/EBPβ Signaling Pathway in Liver Cancer: A Novel Mechanism of Action - Ren, Mudan; McGowan, Eileen; Li, Yarui; Zhu, Xiaofeng; Lu, Xinlan; Zhu, Zhanfang; Lin, Yiguang; He, Shuixiang (Frontiers in Pharmacology, 2019)
Saikosaponin-d (SSd) is an active extract from Radix Bupleuri, the dried root from the plant Bupleurum falcatum used in China for thousands of years to treat liver diseases. The SSd extract possesses valuable pharmacological activities including anti-cancer and anti-inflammatory effects; however, the mechanism underlying the anti-cancer activity of SSd is largely unknown. Here, we explored the mechanism of action of SSd as an anti-cancer agent for liver cancer in two human hepatocellular carcinoma cell lines. Using MTT and annexin-V-FITC/PI assays, Western blots, immunohistochemistry, qRT-PCR, luciferase reporter assay, and a JAK2-specific inhibitor (AG490), we demonstrated that the anti-tumorigenic effects of SSd act through the intermediatory p-STAT3/C/EBPβ signaling pathway to suppress cyclooxygenase (COX)-2. SSd effectively inhibited cell proliferation in a dose-dependent manner. Apoptosis was significantly increased in cells treated with SSd (2.5–15 µg/ml) with concurrent increase and decrease in pro- and anti-apoptosis proteins, respectively. COX-2, C/EBPβ, and p-STAT3 were significantly decreased, at both the translational and transcriptional levels, by SSd treatment. AG490 produced similar inhibitory effects on STAT3, p-STAT3, C/EBPβ, and COX-2. In conclusion, our data suggest that SSd controls liver cancer proliferation through suppression of the p-STAT3/C/EBPβ signaling pathway inhibiting COX2 expression. These findings further our understanding of the pharmacological action of SSd, providing new information on SSd mechanism of action and showing potential for SSd as a novel therapy for liver cancer.